Molecular Docking of Putative Compounds in Aqueous Muntingia calabura L. Leaf Extracts with Cytochrome P450 Proteins - Nas, John Sylvester B; Enriquez, Jose Gabriel Felipe B; Villa-Ignacio, Anton Jose Y; Bungay, Alice Alma C; Salunga, Thucydides L (Asian Journal of Biological and Life Sciences)
Studies claim that Muntingia calabura L. (M. calabura) exhibits antibacterial, antipyretic, antidiabetic, antioxidant, and anti-inflammatory properties. Despite these numerous claims, limited studies have shown its hepatoprotective property. Thus, we investigated the hepatoprotective property of aqueous M. calabura L. leaf extracts (AMCLE) by inhibiting salient CYP450 enzymes associated with hepatotoxicity, CYP3A4 CYP2E1, CYP1A2, and CYP2D6. Aqueous leaf extracts were subjected to phytochemical screening to identify potentially active compounds. A literature search was done to determine the specific metabolites. The identified candidates were docked with CYP450 enzymes virtually. The phytochemical screening revealed that AMCLE contains phenols, tannins, saponins, alkaloids, and flavonoids. The docking experiment showed that galangin, a flavonoid, has the highest binding affinity to the CYP450 enzymes compared to all the putative metabolites tested. Also, galangin outranked most known enzyme inhibitors, except for ritonavir and α-naphthoflavone, inhibitors of CYP3A4 and CYP1A2, respectively. These data suggest that the CYP450-associated hepatoprotective property of AMCLE may be attributed to galangin. Hence, further studies are warranted to support these findings.
Keywords: Cytochrome P450; Hepatoprotection; Hepatotoxicity; Molecular docking; Muntingia calabura.